Real-world outcomes after switching to faricimab in treatment-resistant diabetic macular edema: A 1-year observational study with choroidal thickness assessment - Ryo Tomemori; Hidetsugu Mori; Mari Tanaka; Tatsunori Kiriishi; Masatoshi Omi; Yuki Hattori; Shimpei Oba; Masayuki Ohnaka; Hisanori Imai (PLoS ONE, 2026)
Approximately 40% of diabetic macular edema (DME) cases are resistant to conventional anti-vascular endothelial growth factor (VEGF) therapy. Although faricimab (an antibody against VEGF-A and angiopoietin-2 [Ang-2]) has shown efficacy in treatment-naïve DME, real-world evidence on switching strategies in resistant cases remains limited. We evaluated the 1‑year real‑world effectiveness of switching to faricimab in resistant DME and explored central choroidal thickness (CCT) changes and their relationship to retinal and choroidal responses. This retrospective study included 28 eyes from 19 patients with treatment-resistant DME who switched from aflibercept or ranibizumab to faricimab between May 2022 and August 2023. Central retinal thickness (CRT), CCT, best-corrected visual acuity (BCVA), and injection frequency were evaluated 1 year before, immediately before, and 1 year post-switching. Mean CRT significantly decreased from pre-switching levels of 453 ± 112 μm to 322 ± 60 μm 1-year post-switching (28.9% reduction). The dry macula rate (CRT ≤ 325 μm) was achieved in 53.6% of eyes at 1 year. Injection frequency was significantly higher in the year after switching than in the year before switching (3.5 vs. 5 injections). LogMAR BCVA showed no significant change (0.31 ± 0.27 vs. 0.34 ± 0.32). Ellipsoid zone (EZ)/external limiting membrane (ELM) disruption increased from 28.6% at 1 year before switching to 35.7% immediately before switching, with minimal progression to 39.3% at 1 year post-switching. Mean CCT demonstrated no significant change (238 ± 82 μm vs. 230 ± 62 μm). Faricimab achieved significant anatomical improvements in resistant DME supporting its efficacy in real-world practice. Stable CCT may indicate preserved choroidal perfusion and represent a favorable characteristic of dual VEGF-A and Ang-2 inhibition. The potential suppression of the outer retinal structural deterioration may represent a marker of vascular health during chronic anti-VEGF therapy.